Numerical simulation of brittle damage in concrete specimens - Labadi, Y.; Hannachi, N.E. (Проблемы прочности, 2005)
A framework for damage mechanics of concrete is applied to simulate the non-linear elastic deformation behavior of concrete using finite element method (FEM). A rather simple isotropic damage model containing essentially no adjustable parameters is shown to produce results in remarkably good agreement with sample experimental data: the damage law requires only the fracture energy to be defined completely. The model is achieved by introducing a damage surface that is similar to the yield function in the conventional theory of plasticity. A special form of damage surfaces is constructed to illustrate the application of the model. A new damage criterion, defined as an equivalent strain norm, is proposed, in order to take into consideration the asymmetric behavior of concrete. For verifying the FEM program including the model, deformations predicted by this model are compared with both the experimental ones for the concrete structural model and the ones calculated without application of the continuum damage mechanics.